Probabilistic safety assessment in medical cyclotron facilities - C. Senthil Kumar; Suvadip Roy; Tapan Routh; M. Senthilkumar (Annals of Nuclear Energy, 2026)

A Review on Potato Dormancy Prediction and Sprouting Detection Methods: Advancements in Analytical Technologies for Postharvest Physiology - T. Senthilkumar; S. Ramalingam; R. K. Goraya; U. C. Lohani; C. B. Singh (Potato Research, 2026)

Energy-Efficient Wireless Monitoring and Automated Aeration System for Sustainable Sugar Beet Pile Conditioning - M. Singla; Sunday J. Olakanmi; T. Senthilkumar; S. S. Panigrahi; C. B. Singh (Sugar Tech, 2026)

Impact of lifestyle on salivary microbiota composition and antibiotic resistance in adult periodontitis patients - Saranya S; Saveetha Priya V; Roja B; Shreejaa C; SenthilKumar N; Chellapandi P (Antonie van Leeuwenhoek, 2026)

Experimental and theoretical insights into electronic structure modulated CoMoO4/Mo2TiC2TX-MXene coupling as a dual-functional electrode for supercapattery and oxygen evolution reaction - J. Adithya Shuhruth; P. Nitesh; N. Ambikeswari; C. Sengottaiyan; Masamichi Yoshimura; B. Neppolian; Senthilkumar Ramasamy; Manikandan Kandasamy; T. Kavinkumar (Chemical Engineering Journal, 2026)

Unraveling the multifactorial pathophysiology of polycystic ovary syndrome: exploring lifestyle, prenatal influences, neuroendocrine dysfunction, and post-translational modifications - Harshini Senthilkumar; Subhash C. Chauhan; Mohanapriya Arumugam (Molecular Biology Reports, 2025)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Integrated image segmentation techniques for high-resolution coastal habitat mapping: Advancing remote sensing for coastal ecosystem assessment - Senthilkumar C; Hadeel Alsolai; Randa Allafi; Munya A. Arasi (Journal of South American Earth Sciences, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Coastal spatial planning using object-based image analysis and image classification techniques - Senthilkumar C; Eatedal Alabdulkreem; Nuha Alruwais; Kavitha M (Journal of South American Earth Sciences, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genetic diversity studies between Ipomoea wild species and cultivated sweet potato (Ipomoea batatas (L.) Lam.) using SSR markers - M.S. Amritha; O.G. Dhanya; Aswathy G.H. Nair; P. Vidya; Senthilkumar K. Muthusamy; C. Mohan (South African Journal of Botany, 2024)

Elucidation of novel drought-responsive genes from tuber transcriptome of cassava under water deficit stress - A.V.V. Koundinya; Senthilkumar K. Muthusamy; B.R. Ajeesh; C. Mohan; J. Sreekumar; Sowmya Pulapet; Kesavan Markkandan; M.N. Sheela (South African Journal of Botany, 2024)

Indigenous nutrient supply, weeding and fertilisation strategies influence on-farm N, P and K use efficiency in lowland rice - Thomas Awio; Paul C. Struik; Kalimuthu Senthilkumar; Christian O. Dimkpa; George William Otim-Nape; TjeerdJan Stomph (Nutrient Cycling in Agroecosystems, 2023)
Enhancing use efficiency of applied fertiliser increases farmers’ returns on fertiliser investment through reducing nutrient inputs and improving yields. We investigated on-farm how indigenous nutrient supply and management practices affected N, P, and K uptake, agronomic efficiency and recovery efficiency of fertiliser, and physiological efficiency of nutrients taken up, under irrigated lowland rice conditions in Uganda. Treatments included recommended agronomic practices (RAP) without fertilisation, farmers’ practice (FP), farmers’ selected intensification practice (FIP), and RAP with NPK fertilisation (RAP + NPK). Indigenous N, P, and K supply varied greatly among farmers’ fields. N, P, and K uptake were significantly higher under RAP + NPK than under RAP, FP, and FIP; however, physiological efficiency (PE; kg grain kg −1 nutrient uptake) was significantly lower under RAP + NPK by 19% (N), and 12% (P/K), due to a larger effect of NPK application on uptake than on yield, leading to higher tissue concentrations. Indigenous available N reduced apparent N recovery, and agronomic and physiological N efficiencies independent of treatment. Also, P and K PEs decreased with increasing indigenous supply. Delaying weeding beyond recommended time, in interaction with indigenous N supply, decreased agronomic N efficiency, but increased PE of N. Interaction between P rate and timing reduced its PE; K rate and weeding time interaction reduced its PE. The decrease in efficiencies at high indigenous supply and delayed weeding indicates a need for site-specific fertilisation strategies based on naturally available nutrient levels and proper weeding. Weeding and fertilisation timing directly affect nutrient use efficiency, and therefore, fertiliser use efficiency in rice production systems.

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Genetic control of adventitious rooting traits in bi-parental pedigree of Eucalyptus tereticornis × E. camaldulensis - Varadarajan Muthulakshmi; C. V. Vijayam; Vijaya Kumar Waman Bachpai; Veerasamy Sivakumar; Eswaran Muthulakshmi; Senthilkumar Shanmugavel; Abdul Bari Muneera Parveen; Ramasamy Yasodha; D. Rajasugunasekar; Binai Nagarajan; Annamalai Mayavel; Modhumita Ghosh Dasgupta (New Forests, 2021)

Genome-wide identification of Ran GTPase family genes from wheat (T. aestivum) and their expression profile during developmental stages and abiotic stress conditions - Soham Choudhury; Mansi; Senthilkumar K. Muthusamy; Jasdeep C. Padaria; Monika Dalal (Functional & Integrative Genomics, 2021)

Effects of geological structures on groundwater flow and quality in hardrock regions of northern Tirunelveli district, southern India - M Senthilkumar; R Arumugam; D Gnanasundar; D S C Thambi; E Sampath Kumar (Journal of Earth System Science, 2015)

Preliminary Analysis of Polycyclic Aromatic Hydrocarbons in Air Particles (PM10) in Amritsar, India: Sources, Apportionment, and Possible Risk Implications to Humans - Simerpreet Kaur; Kurunthachalam Senthilkumar; V. K. Verma; Bhupander Kumar; Sanjay Kumar; Jatinder Kaur Katnoria; C. S. Sharma (Archives of Environmental Contamination and Toxicology, 2013)

Methylobacillus rhizosphaerae sp. nov., a novel plant-associated methylotrophic bacterium isolated from rhizosphere of red pepper - M. Madhaiyan; S. Poonguzhali; M. Senthilkumar; D. Pragatheswari; K.-C. Lee; J.-S. Lee (Antonie van Leeuwenhoek, 2013)

Viral and bacterial aetiologies of epithelial ovarian cancer - S. Shanmughapriya; G. SenthilKumar; K. Vinodhini; B. C. Das; N. Vasanthi; K. Natarajaseenivasan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Effects of Copper Sulfate and Copper Nitrate in Aquatic Medium on the Restoration Potential and Accumulation of Copper in Stem Cuttings of the Terrestrial Medicinal Plant, Portulaca Oleracea Linn - S. Mohanapriya; P. Senthilkumar; S. Sivakumar; M. Dineshkumar; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Isolation, PCR based identification, and sensitivity pattern of environmental mycobacteria from leprosy and tuberculosis patients - D. Saravanakumar; N. Elangeswaran; S. Senthilkumar; G. Vanaja; S. Kamakshiammal; C. Chandrasekar; C. N. Deivanayagam; Manjula Sritharan; V. Sritharan (Indian Journal of Clinical Biochemistry, 2000)

Butyltin Compounds in River Otters (Lutra canadensis) from the Northwestern United States - K. Kannan; R. A. Grove; K. Senthilkumar; C. J. Henny; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1999)